The Performance Analysis of Human Resources Higher Education in Kopertis III Jakarta - Prasetio Ariwibowo; Tjipto Djuhartono (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2018)
This study was to find out and understand the profile of Higher Education (PT) Human Resources, the quality of Human Resources for Higher Education, and determine the quality of Higher Education in Kopertis III Jakarta, by using data from 2015 to 2017. The method used in this analysis is a study of documentation and surveys. Besides, key performance indicators (IKU) were used from the Kopertis III Education Strategy Plan in 2015-2019 to assess the quality of Higher Education. The results show that there are 332 Higher Education under the auspices of Kopertis III Jakarta, which consists of PT Private institutions in the form of Universities of 57 Universities, in the form of 15 Institute institutes (4.52%), in the form of Colleges 125 (37.65%), in the form of academies, 121 (36.45%). Based on five composite indicators selected, the quality of PT is only 49.85, meaning less than half. Based on the results of the analysis of the authors, it is recommended that further research is carried out regarding PT data collection, especially lecturers with all the details and whether the composite indicators used are appropriate to measure the quality.